Penerapan Sukuk Mudharabah di Indonesia:Kajian Peluang dan Tantangan dari Sudut Pandang Fiqh Muamalah - Suryani; Al Munawar, M. Itoillah; Fadli Alwi, Ahmad Fadli Alwi (Salam (Islamic Economics Journal), 2026)
The purpose of this study is to determine how the implementation of sukuk in Indonesia is, as well as to discuss the opportunities and challenges of the development of Sukuk Mudharabah. This research uses a qualitative descriptive method by reviewing literature and analyzing data from various sources, including books, the internet, and research journals relevant to the topic. The findings show that Indonesia has demonstrated a strong commitment to developing the Islamic financial market, particularly through the issuance of sukuk. With various types of sukuk, Indonesia has positioned itself as a major player in global Islamic finance and continues to show positive growth. Sukuk Mudharabah, as a profit-sharing-based Islamic financing instrument, has experienced significant development supported by increasing public awareness of Islamic financial products, strong government backing, and innovations in diversifying underlying assets. Despite existing challenges, the issuance of sukuk by both the government and private companies continues to increase, thereby reducing dependence on conventional debt and supporting sustainable projects. A concrete example is the issuance of Sukuk Mudharabah Based on Sustainable Sustainability I by PT Bank Syariah Indonesia Tbk, amounting to IDR 3 trillion. With competitive returns, sukuk mudharabah holds great potential to attract various investor segments, including the younger generation, and can serve as a key instrument in sharia financing that supports economic growth and sustainability in the future.   Keywords : Implementation of Sukuk, Development of Sukuk Mudharabah, Opportunities and Challenges of Sukuk.